PRIORITY OF UNIVERSAL VALUES DURING THE IMPLEMENTATION OF THE IDEA OF INTELLECTUALIZATION FUTURE TEACHER - O.V. Dolzhenko (Academy of Cognitive and Natural Sciences, 2008)
The problem of the professional status of a teacher in the modern world is actualized in this article. The possibilities of the realization of future teachers' intellectualization are considered. The privileges of common-human values in reaching the planetal community are stressed on.